LIABILITY OF LIMITED LIABILITY COMPANIES ADMINISTRATORS - Moreira da Veiga Pessoa, Bruno (Revista Gênero e Interdisciplinaridade, 2023)
The objective of this work is to analyze the form of due diligence of the responsibility of the administrators of limited liability companies. To exercise the established objective, the method used will be deduction, being of a qualitative nature, as for the method of procedure used, it is the monographic one and the research technique is the bibliographic one. The work brings concepts of business partnership, specifies the limited liability company type and demonstrates how administrators work in limited liability companies. Therefore, it is concluded that compliance is a mechanism used as a safeguard against the responsibility of the administrator in the limited liability company, due to the obligation to comply with rules to standardize the conduct of action and reduce reputational and economic risks.